Liquid profiling of circulating tumor DNA in colorectal cancer: steps needed to achieve its full clinical value as standard care. Issue 10 (20th December 2021) - Hedtke, Maren; Pessoa Rejas, Rodrigo; Froelich, Matthias F.; Ast, Volker; Duda, Angelika; Mirbach, Laura; Costina, Victor; Martens, Uwe M.; Hofheinz, Ralf‐Dieter; Neumaier, Michael; Haselmann, Verena
Abstract : The analysis of circulating tumor DNA (ctDNA) is at the threshold of implementation into standard care for colorectal cancer (CRC) patients. However, data about the clinical utility of liquid profiling (LP), its acceptance by clinicians, and its integration into clinical workflows in real‐world settings remain limited. Here, LP tests requested as part of routine care since 2016 were retrospectively evaluated. Results show restrained request behavior that improved moderately over time, as well as reliable diagnostic performance comparable to translational studies, with an overall agreement of 91.7%. Extremely low ctDNA levels at < 0.1% in over 20% of cases, a high frequency of concomitant driver mutations (in up to 14% of cases), and ctDNA levels reflecting the clinical course of disease were revealed. However, certain limitations hampering successful translation of ctDNA into clinical practice were uncovered, including the lack of clinically relevant ctDNA thresholds, appropriate time points of LP requests, and integrative evaluation of ctDNA, imaging, and clinical findings. In conclusion, these results highlight the potential clinical value of LP for CRC patient management and demonstrate issues that need to be addressed for successful long‐term implementation in clinical workflows. Abstract : Liquid profiling (LP) is a promising approach for real‐time assessment of the cumulative tumor mutational profile from a single blood draw. Currently, the workflow is about to be implemented into standard of care for the management of patients with colorectal cancer (CRC), with the aim to better guide CRC diagnostics and optimize therapeutic decisions. Here we report our 5‐year, single medical center clinical experience in LP for CRC patient management.